Interaction Effects of Gender and Motivational Beliefs on Self-Regulated Learning: A Study at ICT-Integrated Schools (Malaysian Journal of Learning and Instruction, 2016)
Purpose â€“ This study aimed to examine the interaction effects of gender and motivational beliefs on studentsâ€™ self-regulated learning. Specifically, three types of motivational beliefs under the Expectancy-Value Model were examined, namely self-efficacy, control beliefs and anxiety. Methodology â€“ A quantitative correlational research design was used to achieve the research objectives. Data were collected through the questionnaire survey method from 322 secondary school students (166 males; 156 females). The samples were taken from two ICT-integrated schools located in Peninsular Malaysia. The learning environment in these schools was conducive for self-regulated learning. The Learning Strategies Scale and the Motivation Scale, taken from the Motivated Strategies for Learning Questionnaire (MSLQ) were used to measure the variables of the study. Findings â€“ The findings showed that self-efficacy and control beliefs were posistively related to studentsâ€™self-regulated learning. Anxiety, however, was found to be negatively related to self-regulated learning. The interactions between gender and levels of motivational beliefs on self-regulated learning were also explored in this study. The relationships between self-efficacy and self-regulated learning differed according to gender. However, there were no significant interaction effects between gender and internal control beliefs on self-regulated learning. This implies that gender differences in self-regulated learning were not due to the differences in control beliefs and anxiety. Significance â€“ This study offers insights on the interaction effects between motivational beliefs, and gender and self-regulated learning. It may helps to develop effective intructional strategies to enhance students' self-regulated learning skill in ICT-related learning environments.